Oral Health-Related Knowledge, Attitudes and Behaviours of Elementary School Teachers - Yılmaz, Gülçin; Riad, Abanoub; Krsek, Martin; Kurt, Hanefı; Attia, Sameh (International journal of environmental research and public health, 2021)
BACKGROUND: elementary schoolteachers play a central role in shaping their students' beliefs, attitudes, and behaviours related to health and oral hygiene. This study was designed to evaluate Turkish schoolteachers' levels of oral health knowledge, attitudes, and behaviours. METHODS: A cross-sectional survey-based study was conducted among elementary schoolteachers in Istanbul using a validated self-administered questionnaire. The questionnaire was composed of 36 multiple-choice items categorised into six sections, and the participants were recruited using convenience sampling. (3) Results: A total of 385 elementary schoolteachers participated in this study. The majority were female (62.2%), qualified with a licensure degree (81.3%) and working in public schools (86.5%). Female gender and greater work experience were found to be promoters for oral health knowledge and positive attitudes. The correlation between their perceived knowledge and actual knowledge was very weak, thus suggesting that the teachers are inclined to overestimate their knowledge. CONCLUSIONS: The Turkish elementary schoolteachers showed satisfactory oral health knowledge and attitudes toward oral health education. The teachers' knowledge about dental trauma management was inadequate, necessitating urgent educational interventions, especially for physical education teachers, who are at the greatest risk of encountering such events during their work. The oral hygiene behaviours were not associated with teachers' oral health knowledge, attitudes, or practice, thus requiring further investigation.
Keywords: Oral Health; Health Education, Dental; orální zdraví; průřezové studie; lidé; Cross-Sectional Studies; zdravotní výchova zubní; učitelé; průzkumy a dotazníky; zdraví - znalosti, postoje, praxe; Humans; Surveys and Questionnaires; Male; School Teachers; mužské pohlaví; Health Knowledge, Attitudes, Practice; ženské pohlaví; Female